A study on the differences in the levels of computer anxiety and computer literacy due to demographic factors among employees in Mulu National Park, Sarawak - Laing Epoi, Edward (2000)
The purpose of this study was to describe the differences in the levels of Computer Anxiety and Computer Literacy due to demographic factors among employees in Mulu National Park, Miri, Sarawak. The demographic features investigated were gender, age groups, highest academic qualification, working experience, computer experience with different software, number of computer course attended and computer ownership. A survey questionnaire adapted from the Lindsay Unified School District Technology Literacy Survey (1999) was used to elicit information from 138 respondents.